Epilepsy in the elderly: restrictions, fears, and quality of life - May, T. W.; Pfaefflin, M.; Brandt, Christian; Fueratsch, N.; Schmitz, B.; Wandschneider, B.; Kretz, R.; Runge, U.; Geithner, J.; Karakizlis, H.; Rosenow, F.; Kerling, F.; et al. (Acta Neurologica Scandinavica, 2015)
Due to demographic change and high incidence of epilepsy in elderly, the number of elderly with epilepsies is increasing. However, only few studies investigated the impact of epilepsy on quality of life (QoL). We investigated how epilepsy affects different aspects of QoL dependent on the age of the patients and the age of onset of epilepsy.In a multicenter, cross-sectional study, three patient groups were recruited from five centers: Group A1: 45 elderly (>=65 years.) with late onset of epilepsy (>=65 years), group A2: 51 elderly (>=65 years.) with early-onset, long-lasting epilepsy (<=50 years), group B: 41 young adults (<=50 years) with epilepsy. Statistical analysis of differences between groups was performed using generalized linear models.Elderly with late-onset epilepsy (group A1) had a significantly lower seizure frequency, were treated with less anti-epileptic drugs (AEDs), and reported a better tolerability of AED treatment, but had more comorbidities compared with groups A2 and B. After adjusting for seizure frequency, tolerability of AEDs and comorbidity, young adults (group B) reported the highest overall QoL, whereas patients of group A1 and A2 did not differ significantly. Epilepsy-related fears, especially fears of stigmatization, were significantly higher in elderly with long-lasting epilepsy compared with groups A1 and B.Seizure-related variables, tolerability of AEDs and comorbidity have a stronger impact on QoL and on restrictions due to epilepsy than age, age at onset of epilepsy or duration of epilepsy. However, some results indicate group-specific patterns of impairment and epilepsy-related fears.
EVALuna2:22415